APPLICATION OF VIRTUAL ENVIRONMENTS IN TRAINING OF ERGATIC SYSTEM OPERATORS - Petukhov, Igor; Steshina, Lyudmila; Glazyrin, Andrei (Journal of Applied Engineering Science, 2018)
The paper discusses the approach to the training of ergatic system operators, which implies the application of virtual reality elements. It presents the review of the existing models of the virtual environment application, offers a system model of the operator's response, systemizes the main structural and functional elements of personal experience in virtual environments.The research outcomes are obtained by the support of RF Ministry of Education and Science grant No. 25.1095.2017/4.6
Keywords: virtual reality; virtual environment; human-operator; Ergatic control systems